Sign, a Visual Analysis of Public Signage in New Zealand - Gielen-Recoules, Greet (Auckland University of Technology, 2012)
Through an investigation of the regulatory and informative signs which constitute public signage in rural New Zealand, this creative research project poses the question: When is a public sign not a public sign? The research explores the function of the graphic elements that are commonly presented in a public signage, and questions how messages are communicated through these related signifiers. The intention of this research is to explore how meaning is constructed in public signage and how new meanings can be created by means of subtraction, isolation and juxtaposition. Through these investigations I intend to locate the point where the meaning of the public sign changes. To locate the point where the function of the sign changes. To locate the point when the public sign is not a public sign. The aim of this research is to develop a deeper understanding of how the meaning making process operates in the graphic design of public signage and it is intended that my findings will make a contribution to the body of Knowledge in this field.
Keywords: Graphic design; Rural and urban; Interpretation of meaning; Metonymy; Synecdoche; Public signage